Nonlinear effects of pandemic uncertainty on depression, pandemic preventive behavior intentions, and positive life attitudes: Moderating effects of high and low uncertainty grouping - Liu, Zeyu; Liu, Yun; Li, Ang; Zhu, Tingshao (Frontiers in Public Health, 2023)
As it is difficult to end COVID-19 in a short time, people are facing two major uncertainties: (a) uncertainty about the spread of the pandemic and their infection, and (b) uncertainty about the future development of the pandemic. Understanding the influence of uncertainty on people’s psychological outcomes will help people to restore a healthy and orderly life state. Past relevant studies mainly focused on the sense of control and intolerance of uncertainty. However, these two concepts will be more influenced by other factors (such as factors related to individuals’ work, education, or children’s development) in the current situation when people’s lives are gradually returning to normal. And it is difficult to accurately reflect the individuals’ perceptions of uncertainty during the pandemic. As a result, we propose the concept of “pandemic uncertainty” and investigate its impact on people’s daily lives. Besides, we also found that research conducted in the early stages of the outbreak investigated the relationship between outbreak uncertainty and people’s psychological states at higher levels of uncertainty. We don’t know if the effect of uncertainty on psychological states differs between high and low levels of uncertainty. To address this question, this study obtained data about uncertainty, depression, positive attitude, pandemic preventive behavior intentions, personality, and social support from 530 subjects. Firstly, according to the distribution of uncertainty, we divided the dataset into high and low groups. Subsequently, by using uncertainty as the independent variable, the grouping variable as the moderating variable, and other variables as the control variables, the moderating effects were analyzed for depression, positive attitude, and pandemic preventive behavior intentions, respectively. The results showed that the grouping variable significantly moderate the influence of uncertainty on positive attitude and pandemic preventive behavior intentions but had no significant effect on depression. Simple slope analysis revealed that high grouping uncertainty significantly and positively predicted positive attitude and pandemic preventive behavior intentions, while low grouping effects were not significant. These results reveal a nonlinear effect of pandemic uncertainty on the pandemic preventive behavior intentions and positive life attitudes and enlighten us about the nonlinear relationship of psychological characteristics during a pandemic.